Trust and involvement of Cameroonian software developers in open-source projects - Martial Kadji Ngassam (Data Science and Management)
Although recent studies have examined collaboration within open-source software projects, the focus has primarily been on their motivations and governance. This study explores the complex dynamics of trust and involvement among Cameroonian software developers in open-source projects. In the context of a rapidly evolving software development landscape, these projects have emerged as a transformative force, redefining global collaboration standards. The qualitative methodological approach involved a survey of 22 participants in open-source software projects, including Cameroonian software developers, project governance actors, and open-source community members. Analyses revealed that the trust given to African software developers, including their effective integration into projects and consideration of their specificities and contributions, has a positive impact on their involvement in and ability to appropriate information technologies. By exploring the interaction between cultural, social, and technological factors, this study enhances our understanding of trust mechanisms within open-source communities, especially those involving remote developers.